2018
DOI: 10.1111/aji.13030
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid proteomic signatures of cervical insufficiency and their association with length of latency

Abstract: In this pilot study, significant differences in the amniotic fluid proteomic profiles in cases of cervical insufficiency compared to genetic amniocentesis were observed. Proteomic signatures were predictive of achieving latency > 1 week after diagnosis of cervical insufficiency. These preliminary findings suggest that proteomic analysis may be of value in predicting outcome following cervical insufficiency and warrants further validation in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Similar to our results, Govia et al . analyzed proteomic profiling of AF using normal pregnancy (genetic amniocentesis) as a control group and found chemotaxis, homing of leukocytes, activation of cells, and inflammatory response as the top activated biological functions associated with CI [ 66 ]. Taken together, these IPA data suggest that inflammatory and immune responses that have occurred in the uterine cavity may play an important role in the process of premature cervical dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Govia et al . analyzed proteomic profiling of AF using normal pregnancy (genetic amniocentesis) as a control group and found chemotaxis, homing of leukocytes, activation of cells, and inflammatory response as the top activated biological functions associated with CI [ 66 ]. Taken together, these IPA data suggest that inflammatory and immune responses that have occurred in the uterine cavity may play an important role in the process of premature cervical dilation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a solid body of evidence showing that the presence of intra-amniotic inflammation in pregnancies with cervical insufficiency with prolapsed fetal membranes is associated with a shorter interval between amniocentesis and delivery [4, 12, 13, 17, 37, 38], lower gestational age at sampling [4, 11, 13, 14, 17], and higher rates of preterm deliveries [4, 12, 13, 17, 37]. These findings were also confirmed by our study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that peripheral CRP levels (≥4 mg/L) and WBC counts (≥10,000/mm 3 ) were associated with a significantly decreased likelihood of delivery at and after 28 weeks gestation [79]. Some authors expect that Gram's method and culture of amniotic fluid are imperfect techniques to detect infection in patients with cervical insufficiency that are qualified to emergency cerclage procedure [81]. Proteomic profiling of amniotic fluid could be better solution in that cases.…”
Section: Risk Factors Of the Emergency Suture Failurementioning
confidence: 99%